Nulidad de transferencia de bienes para evitar el pago de la reparación civil de la víctima - Sotelo Mudarra, Luis Alberto (2014)
The invalidity of the transfer of property is an act by which will request that an act of alienation voided, and be restored to its previous owner. The investigation considered whether this figure is that guaranteed the right of the victim of a crime to civil damages as a result of the damage that has been caused. In the results that came after analyzing each of the stages of the common criminal proceedings as well as the actual implementation of the various precautionary measures, was that such action if it guarantees the right to have the victim civil damages. The conclusions to be established is that the stage can raise this figure to the invalidity of transfer of property is ideal for in them standing is given to each party to the crime victim can present their evidence means to prove damages they have caused, they will then be actuated, which could also raise this action against the third party liable